School Nurses' Experiences of Health Promotion for School-Age Asylum Seekers - Inkeroinen Saija; Hupli Maija; Stolt Minna (United States, 2022)
The number of school-age asylum seekers and refugees worldwide is increasing. Health promotion provided by school nurses can be crucial for the well-being of young asylum seekers, yet research on these nurses' experiences is limited. This qualitative study aims to describe school nurses' experiences of providing health promotion to school-age asylum seekers. Semistructured interviews were conducted with 12 school nurses, and inductive content analysis was then used. The results were grouped under the following themes: (1) difficulties in providing health services to school-age asylum seekers, (2) considering the vulnerable circumstances of asylum seekers, (3) the importance of family-centered health promotion, and (4) the importance of time management. School nurses face challenges that stem from individual asylum seekers' unique circumstances, nursing competency, and the school health care system. To deepen the existing knowledge, further research is needed from the perspective of asylum seekers.